Change Process in Malaysia Airlines System (MAS) / Nadhilah Mahmood, Haneesah Rostam and Fhathin Syazwanie Izhar - Mahmood, Nadhilah; Rostam, Haneesah; Izhar, Fhathin Syazwanie (2008)
In 1994 Malaysian entrepreneur Tajudin Ramli bought a 32 percent controlling interest for M$2 billion ($745 million) worth of stock. The government retained an 11 percent interest. Tajudin, who had earlier put together a mini-aviation empire in preparation of competing with MAS, was saddled with an overlarge fleet and diminishing profits. Although sales rose to $M4.1 billion ($1.6 billion) in the fiscal year ending March 3, 1994, profits fell from M$145.4 million ($56.4 million) to M$7.7 million ($2.9 million). The carrier was still receiving large shipments of new aircraft, including Boeing 747s, and sales of its used aircraft were slow. (Some of MAS's new A330 aircraft were delivered late, resulting in penalty payments from Airbus.) Tajudin immediately set out to trim the fat. He introduced a more businesslike attitude and required better reporting from the company's managers. Aircraft utilization was increased. The carrier signed code-share agreements on transpacific routes and promoted its Kuala-Lumpur-Los Angeles route to attract more business passengers. Virgin Atlantic Airways teamed with MAS in 1995 to operate joint London-Kuala Lumpur flights. The service proved convenient for Virgin's Australia-bound passengers. Planes stayed just as full after the number of flights was increased from eight to 14 a week, although the two carriers faced very formidable competition from the British Airways/Qantas alliance, which operated the only single-plane service between London and Australia. MAS recorded its highest ever pretax profit in 1996--97 of M$349.4 million ($120 million). The company continued to buy new planes and relocated to Kuala Lumpur's new Sepang International Airport, a move expected to further enhance its reputation. However, the new airport's opening was plagued with lost baggage, computer malfunctions, and other annoyances